2018
DOI: 10.1002/jctb.5796
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aniline contaminated water by a self‐designed dielectric barrier discharge reactor coupling with micro‐bubbles: optimization of the system and effects of water matrix

Abstract: BACKGROUND A self‐designed dielectric barrier discharge reactor coupling with micro‐bubbles (DBD/MB) system is proposed as a promising method to remove aniline in waste water. The optimum geometric dimensions of the reactor and the operating parameters of the DBD/MB system as well as the influence of the water matrix (including cations, anions, and coexisting organics) were investigated. The functional mechanisms of the DBD/MB system were explored. RESULTS By setting the double‐dielectric barrier discharge rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 45 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…(b)]. Because elevated conductivity hinders effective degradation of organic chemicals, a decrease in conductivity as a result of CaO 2 addition provides a conducive environment that enhances GC removal during DBD/CaO 2 treatment. Similar observations, that addition of CaCl 2 increased the wastewater purifying ratio while using nonthermal plasma treatment, were made by Qi et al.…”
Section: Resultsmentioning
confidence: 99%
“…(b)]. Because elevated conductivity hinders effective degradation of organic chemicals, a decrease in conductivity as a result of CaO 2 addition provides a conducive environment that enhances GC removal during DBD/CaO 2 treatment. Similar observations, that addition of CaCl 2 increased the wastewater purifying ratio while using nonthermal plasma treatment, were made by Qi et al.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of the surface charges (ζ potentials) of the MBs, which were measured during their collapse, supported the hypothesis that the significant increase in ion concentration around the shrinking gas-water interface provided the mechanism for radical generation. Studies showed that compared with plasma treatment alone, the presence of MBs can significantly improve the treatment efficiency, and preliminary studies speculate that the presence of MBs can improve gas-liquid mass transfer in plasma water treatment [154,155]. MBs were introduced with different carrier gases (air, N2 and Ar) in the needleplate pulsed discharge reactor to enhance the interface reaction [156].…”
Section: Heterogeneous Catalystmentioning
confidence: 99%
“…In addition to the different molecular structures of pollutants, the design and experimental conditions of a nonthermal plasma reactor also have a great influence. Due to the particularity of in situ Studies showed that compared with plasma treatment alone, the presence of MBs can significantly improve the treatment efficiency, and preliminary studies speculate that the presence of MBs can improve gas-liquid mass transfer in plasma water treatment [154,155]. MBs were introduced with different carrier gases (air, N 2 and Ar) in the needle-plate pulsed discharge reactor to enhance the interface reaction [156].…”
Section: Practical Implications Of This Studymentioning
confidence: 99%
“…This investigation might be the first documented study of the discharge plasma-liquid interactions. Since then, applications of the plasma-liquid systems have been extensively explored [2], such as in wastewater treatment [3][4][5][6][7][8][9][10][11][12], nanomaterial synthesis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], plasma medicine [30,31], plasma agriculture [32,33], and analytical chemistry [34][35][36][37][38][39][40][41][42]. These applications are mainly based on the physical and chemical processes induced by the interplay between the plasma and the liquid.…”
Section: Introductionmentioning
confidence: 99%